2011
DOI: 10.1111/j.1442-2050.2011.01261.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonmuscle myosin IIA is associated with poor prognosis of esophageal squamous cancer

Abstract: Nonmuscle myosin IIA (myosin IIA) is a force-producing protein involved in the process of cell migration. Its expression has been considered as a bad prognostic indicator in stage I lung adenocarcinoma. However, the expression and clinical significance of myosin IIA in esophageal cancer has not been explored. In this study, we investigate the expression level of myosin IIA in 50 esophageal squamous cancer and 30 adjacent normal esophageal tissues by immunohistochemical staining and correlated its expression wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 30 publications
11
39
0
Order By: Relevance
“…Here, we find that high MYH9 expressers harbored poor overall survival in two different cohorts. These results were consistent with several recent reports showing that high expression of MYH9 was correlated with short survival in solid tumors [7, 9, 10]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we find that high MYH9 expressers harbored poor overall survival in two different cohorts. These results were consistent with several recent reports showing that high expression of MYH9 was correlated with short survival in solid tumors [7, 9, 10]. …”
Section: Discussionsupporting
confidence: 93%
“…With respect to expression value of MYH9 , it was reported that reduced expression of myosin-9 was exhibited in CLL samples from high-risk patients. In contrast, high MYH9 expression was associated with poor clinical outcome in patients with several tumors such as lung cancer [6], esophageal [7], bladder [8], gastric cancer [9] and malignant pleural mesothelioma [5]. However, the clinical significance of MYH9 expression in AML is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Myosin-9 has been reported to be a target for anti-invasive treatment in human MCF-7 breast cancer cells [34] and gastric cancer [35]. High expression of myosin-9 is correlated with short survival in lung adenocarcinoma and ESCC [36], similar to our results.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, NM2B was recently shown to be important for nuclear translocation during 3D invasion, while NM2A was required for generating traction forces during intial adhesion and spreading [41]. While no changes to NM2B have so far been reported in cancer, increased expression levels of NM2A have been linked to gastric cancer [42], non small cell lung cancer [43], oesophageal [44] and bladder cancer [45], while decreased levels are associated with squamous cell carcinomas [46], where NM2A was identified as a tumour suppressor. In contrast, expression levels of NM2A were the same for a range of LNCaP, PC3 and DU145 prostate cancer cell lines, and were unchanged in prostate cancer tissues with low and high metastatic potential [5].…”
Section: Class 2 Non-muscle (Nm) Myosin Isoformsmentioning
confidence: 99%